Exports, R&D and productivity in German business services firms: A test of the Bustos-model - Alexander Vogel; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This paper uses newly available data for German business services firms to test a hypothesis derived by Bustos (AER 2011) in a model that explains the decision of heterogeneous firms to export and to engage in R&D. Using a non-parametric test for first order stochastic dominance it is shown that, in line with this hypothesis, the productivity distribution of firms with exports and R&D dominates that of exporters without R&D, which in turn dominates that of firms that neither export nor engage in R&D. These results are in line with findings for firms from manufacturing industries. The model, therefore, seems to be useful to guide empirical work on the relation between exports, R&D and productivity for services firms, too.
Keywords: F14; 330; Exports; R&D; productivity; business services firms; Germany; Unternehmensdienstleistung; Produktivität; Forschung; Internationaler Dienstleistungsverkehr; Export; Deutschland